(3GdeNJUQ aj Yde CUhd GdMOjKs - (3GHf GdfajS , YdGA GdOjf CHh GdMSf Ydj Hf CHj GdMRe GdbQTj, GHf GdfajS,J (B687 (3g` s
(3ChdgG (B:s
(3aEfi CQjO Cf CPcQ ai gPG GdcJGH ef CUhd Yde GdMOjK hQJHJg Ydi ebOeI hNeSI CHhGH s
(3BNQgG (B:s
(3hcGf QShd Gddg bO bGd Ci GdCbhGd Pdc hcPdc EPG Qhi Yf QShd Gddg Je GdeNJUQ ai Yde CUhd GdMOjK s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B58s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY (B209) s
Keywords: (3GdMOjK h GdeUWdMs